Discovering External Motivation in EFL Students Toward Word Target and Reading Pleasure Using Xreading Application - Bakiyatus Solihah; Pratiwi Retnaningdyah; Ahmad Munir (LP. Ma'arif Janggan Magetan, 2024)
This study explores foreign language students' external motivation in extensive reading related to word targets and reading enjoyment. This research aims to find out how word targetss become assessments that can motivate foreign language students to enjoy reading. Extensive reading is not related to assessments that require foreign language students to be motivated to read. This research is qualitative research. The participants in this research were students in the A-class students of the English language and literature education study program at a university in Surabaya, Indonesia. The data collected is in the form of interview data and student reading profiles recorded in the Xreading application. Xreading is an application that students use as a learning management system in their extensive reading process. Xreading can also provide a place for foreign language students to determine what they want to read according to their pleasure. The results of this research found that students used target words as their external motivation to enjoy reading. The findings in this research also suggest ongoing monitoring by lecturers so that foreign language students continue to be motivated and enjoy reading so that their reading progress continues to increase.